The Eurocentric Religions’ Multiparous in African System of Governance in Mongo Béti And Ahmadou Kourouma’s Selected Novels - Babayemi, John Babatunde (NIU Journal of Humanities, 2020)
Eurocentric religion is the belief in the eminence of foreign religion over the existing or â€œnativeâ€ religion; giving birth to more than one adverse effect on African peace. Existing studies have examined revolt and oppression of Africans by Foreigners in francophone African novels with little attention paid to the domineering power of the foreign religions over African community. This study, therefore, is designed to examine the Eurocentric religionsâ€™ multiparous in African system of governance in Mongo BÃ©ti and Ahmadou Kouroumaâ€™s selected Novels  with a view to establishing the denigration of foreign religions and the havoc caused in Francophone African society, and their implications on contemporary Africa. Postcolonialism and Realism theories were adopted as framework. BÃ©tiâ€™s Le Pauvre Christ de Bomba and Le Roi MiraculÃ©,; Kouroumaâ€™s Allah nâ€™est pas obligÃ© and Quand on Refuse on dit Non were purposively selected because they are novels of religions denunciation. Close reading was adopted as methodology. Data were subjected to literary analysis. In conclusion, we discovered that African system of governance has been taken over by the colonisers and this cause the reason they are still â€œobserversâ€ during African election process till date. Human entity been depersonalised to the extent that he leaves his comfort, spending his fortunes to perform pilgrimage to â€œHoly landsâ€. BÃ©ti and Kourouma portrayed alien religions as causes of disunity, war, hypocrisy, subjugation of African culture other than agents of peace, unity and progress and this is the bane of the contemporary Francophone African societies. Keyword : Eurocentric, Multiparous, Peace and Conflict, Religion, Slavery